Education and Depression Screening for Adolescents Based on Smartphone Applications: A Scoping Review - Hilda Octri Nurahmah; Ni Nyoman Armelia Dewi; Afifah Chairany; Ima Safitri Puji Utami (Indonesian Journal of Global Health Research, 2025)
Depression is the leading cause of disability among adolescents. Many adolescents experience long-term mental health issues because they do not know what to do, leading many to engage in negative behaviors such as substance abuse, violence, criminal activities, dropping out of school, and more. This is due to the lack of information they receive regarding mental health issues. Method: A scoping review was conducted by searching literature in PubMed, ProQuest, Scopus, and Science Direct. Included studies (2020–2025) explored education and depression screening for adolescents based on smartphone applications. Excluded were incomplete, duplicate, review, and retracted articles. Results: Of the 2,128 identified articles, seven studies met the criteria for further analysis. Findings indicate that education methods based on digital applications can be utilized as tools for early screening, monitoring, and real-time evaluation of depressive symptoms to support the mental well-being of adolescents. By integrating technology and evidence-based practices, these applications provide psychoeducational tools and self-monitoring mechanisms to help adolescents effectively manage their mental health. Conclusions: Education and smartphone-based depression screening can enhance sustainable support for adolescents. The importance of using smartphone applications in education and depression screening for adolescents indicates that technology-based applications can be effective tools for supporting the mental well-being of young people by providing easier access and reducing stigma associated with mental health services.